The Integration of Knowledge in Islam : Concept and Challenges (Global Journal of Human-Social Science, 2013)
Integration is an approach process which can be used in the educational sector to create a madani generation of multidisciplinary knowledge Integration is defined as a merger between two or several races factors sectors etc as a union or consolidation The Muslims are obligated to master various forms of knowledge beginning with the Islamic traditional knowledge of faith akidah syariah and morals akhlak The understanding of the Islamic knowledge together with that of the modern world s can lead to the emergence of new modern knowledge in line with Islamic requirements Islam never forbids the Muslims to learn foreign knowledge in fact it is highly recommended This paper hopes to highlight the concept of integration of knowledge from Islamic perspectives and the challenges that need to be addressed to make it a reality for the society The application of western knowledge leads to the spread of secularinfluence in the educational system of a nation which in turn leads to the gradual loss of Islamic identity of the society Therefore the approach to the integration of Islamic knowledge and that of the West needs to be seen as an alternative for the society in leading their everyday lives based on the true teachings of Islam
Keywords: integration; knowledge; islam and the west